P-OGC74 Effect of pre-operative anaemia on short-term outcomes following oesophagectomy: a 10-year retrospective cohort study. (16th December 2021) - Chien, Siobhan; Khan, Khurram; Gall, Lewis; Deboys, Liam; Craig, Carol; MacKay, Colin; Macdonald, Andrew; Forshaw, Matthew
Abstract: Background: Pre-operative anaemia is associated with increased length of hospital stay, requirement for allogenic blood transfusion, post-operative complications and mortality. Oesophagectomy is a complex procedure associated with significant physiological insult, thus pre-operative patient optimisation is imperative to improve clinical outcomes. This study aimed to determine the impact of pre-operative anaemia on short-term outcomes following oesophagectomy for benign and malignant disease.  Methods: A retrospective cohort study of all oesophagectomies performed in a single tertiary referral centre between 1 January 2010 and 31 December 2019 was performed. Patients were identified from a prospectively collected database and individual patient electronic records were interrogated. Patients were dichotomised into two groups, based on the most recent pre-operative haemoglobin. Patients with pre-operative anaemia (haemoglobin <130mg/L in males and <120mg/L in females) were compared to those without pre-operative anaemia. Patients with missing data were excluded from the study. Patients were followed up for a median of 32 months (IQR 18-66). Results: Of 352 patients eligible for inclusion, 173 (49.1%) patients were anaemic immediately pre-operatively. Patients with pre-operative anaemia were older (66 vs. 64 years, p = 0.031), with a lower anaerobic threshold (11.7 vs. 12.3ml/min/kg, p = 0.011), and were significantly more likely to have undergone neoadjuvant chemotherapy (91.3% vs. 78.8%, p < 0.001). Patient comorbidities and disease-related characteristics were similar between the two groups. Patients with pre-operative anaemia were significantly more likely to require post-operative blood transfusion (34.7% vs. 16.8%; p < 0.001). However, pre-operative anaemia was not associated with increased post-operative complications, intensive care admission, length of hospital stay, or 30- and 90-day mortality rates following oesophagectomy. Conclusions: Patients with anaemia immediately prior to undergoing an oesophagectomy were significantly more likely to require post-operative blood transfusion. However, pre-operative anaemia was not associated with an increased rate of post-operative morbidity or mortality. In addition, pre-operative iron transfusion is becoming increasingly utilised to minimise the incidence of pre-operative anaemia: this was not analysed in this study.